Energy performance evaluation of heat storage of calcium sulfate hemihydrate composite with fine aggregate based on paraffinic phase change material. (October 2021) - Jeong, Su-Gwang; Wi, Seunghwan; Chang, Seong Jin; Kim, Sumin
Abstract: Calcium sulfate hemihydrate has been used as a building material because of its economical and non-combustible characteristics. By applying a heat storage material to a calcium sulfate hemihydrate composite (CSHC), the building energy consumption can be reduced. In this study, a CSHC with a high heat storage capacity was prepared using fine aggregates based on paraffinic shape-stabilized phase change materials (Fa-PSSPCMs) with exfoliated graphite nanoplatelets as stabilizing additives. The heat storage CSHC (Hs-CSHC) was prepared by mixing Fa-PSSPCM and calcium sulfate hemihydrate powder with water and then casting the mixture as boards using molds. For the Hs-CSHC containing 30 wt% Fa-PSSPCM, the latent heat capacities during heating and cooling were 46.39 and 44.28 J/g, respectively; its phase transition occurred at 20–35 °C. Based on analysis results, the Hs-CSHC exhibited acceptable chemical stability and high thermal performance, including a considerable latent heat capacity. The peak temperatures of Hs-CSHCs were approximately 1–2 °C lower than those of the plain CSHC. Moreover, compared with the plain CSHC, the Hs-CSHC with 30 wt% Fa-PSSPCM exhibited a time lag effect exceeding 720 min. In the energy simulation analysis, an 8.18% maximum cooling energy reduction was observed when the Hs-CSHC with 30 wt% Fa-PSSPCM was used. However, the effect of heating load reduction was insignificant due to the low outside temperature. Therefore, when a phase change material is utilized in a building, the phase change temperature and heat storage performance must be considered. Highlights: Hs-CSHCs were made by physical bonding with Fa-PSSPCM aggregate. Maximum latent heat capacities during heating and cooling were 46.39 and 44.28 J/g. Peak temperature reduction and time lag effect were confirmed in heat transfer analysis. Hs-CSHCs were applied to a wood frame house for energy performance evaluation. In the simulation analysis, a maximum cooling energy reduction of 8.18% was observed.